Demographic factors in connection with instructional leadership practiced by secondary school principals - Baharuddin, Juliana; Don, Yahya; Mohamad Zain, Farah (Eximia, 2022)
The purpose of this study was to determine the level of instructional leadership among Kelantan secondary school principals. A total of 375 teachers from Kelantan’s secondary schools participated in this survey. Instructional leadership is a type of leadership that promotes and facilitates learning in the classroom. The Principal Instructional Management Rating Scale (PIMRS) by Hallinger and Murphy, 1985, is the instrument used to study instructional leadership. The instrument is originally an English-language instrument which has been translated into Malay. Statistical Packages for the Social Sciences (SPSS) version 22.0 was used to examine all of the data and details gathered. Descriptive Mean Test, T-test, and One-Way ANOVA were used in the data analysis. The data exhibited a high level of instructional leadership. Male principals and female principals have nearly comparable levels of instructional leadership practise. In comparison to older principals, the survey discovered that those between the ages of 26 and 30 had the highest level of instructional leadership. Principals who have been in charge of a school for 5-7 years have the most instructional leadership skills. This study recommends that stakeholders such as the Ministry of Education, the State Education Department, and the District Education Office adopt principals’ professional development courses, which will result in an increase in instructional leadership principals.